Acinic Cell Carcinoma of the Breast: Report of a Case With Immunohistochemical and Next-Generation Sequencing Studies. (December 2021) - Weaver, Kaitlin D.; Isom, James; Esnakula, Ashwini; Daily, Karen; Asirvatham, Jaya R.
Acinic cell carcinoma of the breast is a rare subtype of triple-negative breast cancer that recapitulates the appearance of tumors seen in salivary glands. We present the case of a 42-year-old woman with an irregular, nontender mass above the left nipple during routine obstetric appointment at 24 weeks gestation. She was subsequently diagnosed with triple-negative invasive ductal carcinoma of the left breast, Nottingham grade 3, via core needle biopsy. She was treated with neoadjuvant therapy (doxorubucin and cyclophosphamide) antenatally and paclitaxel in the postpartum period followed by left mastectomy with sentinel node biopsy. The carcinoma in the mastectomy specimen showed a spectrum of morphologic patterns with immunohistochemistry revealing strong positivity for alpha-1-antichymotrypsin, epithelial membrane antigen (EMA), lysozyme, and S100. The histomorphology paired with the immunoprofile led us to the diagnosis of acinic cell carcinoma. We retrospectively performed immunostains in the core biopsy specimen, which demonstrated GATA-3 and DOG-1 positivity. Next-generation sequencing of the postneoadjuvant specimen using a 70-gene panel revealed 2 single-nucleotide variant (SNV) mutations: tumor protein 53 (TP53) (c.747G>T) SNV mutation and rearranged during transfection (RET) (c.2899G>A) SNV mutation.